2009
DOI: 10.1051/radiopro/20095054
|View full text |Cite
|
Sign up to set email alerts
|

A return to the nuclear waste dumping sites in the bays of Novaya Zemlya

Abstract: Abstract.A new assessment of the nuclear dumping sites of Novaya Zemlya was performed in 2003/4. 137 Cs contamination levels within both Stepovogo and Abrosimova Bays are similar to background environmental levels and there has been no detectable leakage from objects in Tsivolki Bay. Near-surface sediment 137 Cs contamination levels in 2003/04 are 1-11 Bq/kg, 4-268 Bq/kg, and 13-20 Bq/kg in Tsivolki, Stepovogo and Abrosimova Bays respectively. These conclusions are further supported by the data for 238 Pu and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…S6). On a global scale, higher and Dachs, 2007a) and from 0.01 to 0.8 cm s −1 in coastal areas (Holsen and Noll, 1992;Bozlaker et al, 2008;Esen et al, 2008;Eng et al, 2014); the higher values were observed in concentrated industrial and urban areas (Bozlaker et al, 2008). In our study, the highest V d values were observed in the Barents Sea; the other three seas had similar V d values (p > 0.05) that were lower than in the Barents Sea except for 9-methylfluorene and 1,7-dimethylfluorene.…”
Section: Pahs In the Atmosphere And Oceanmentioning
confidence: 99%
“…S6). On a global scale, higher and Dachs, 2007a) and from 0.01 to 0.8 cm s −1 in coastal areas (Holsen and Noll, 1992;Bozlaker et al, 2008;Esen et al, 2008;Eng et al, 2014); the higher values were observed in concentrated industrial and urban areas (Bozlaker et al, 2008). In our study, the highest V d values were observed in the Barents Sea; the other three seas had similar V d values (p > 0.05) that were lower than in the Barents Sea except for 9-methylfluorene and 1,7-dimethylfluorene.…”
Section: Pahs In the Atmosphere And Oceanmentioning
confidence: 99%
“…3 ). Besides nuclear tests, various types of nuclear waste have been buried in soil and shores of Novaya Zemlya [ 27 , 28 ]. Data on soil radioactive contamination in Novaya Zemlya is scarce [ 29 ], but contaminated areas are reported at least near nuclear waste dumping sites [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides nuclear tests, various types of nuclear waste have been buried in soil and shores of Novaya Zemlya [ 27 , 28 ]. Data on soil radioactive contamination in Novaya Zemlya is scarce [ 29 ], but contaminated areas are reported at least near nuclear waste dumping sites [ 28 ]. A large part of the taiga bean goose population thus gathers annually to an area that has exposed the population to the direct effects of detonations, nuclear fallouts and leaks of nuclear waste.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide concentrations in aquatic ecosystems in sea areas nearby Novaya Zemlya have been well investigated. For instance, Russian researchers (Matishov et al 1994a , 2020 , 2021 ), a joint long-term Norwegian-Russian co-operation (JRNEG 1994 , 1996 ; Strand et al 1994 ; Salbu et al 1997 ; Dahle et al 2009 ; JNREG 2014 ; Gwynn et al 2016 ; Heldal et al 2018 ), Polish-Russian co-operation (Matishov et al 1994b ; Szczypa and Reszka 1998 ), and Finnish-Russian co-operation (Matishov et al 1995 , 2011 ; Leppänen et al 2013 ) have improved knowledge about radioecology in these aquatic ecosystems. It has been found in these studies that radionuclide concentrations in aquatic environment in Russian Arctic regions have been generally at a low level, not significantly deviating from the radioactivity levels due to global fallout.…”
Section: Introductionmentioning
confidence: 99%